A COMPARATIVE STUDY ON TURKEY’S NATIONAL GREEN BUILDING CERTIFICATION SYSTEM UNDER ENERGY POLICY DEVELOPMENTS - Filiz Umaroğulları; Semiha Kartal; Dinçer Aydın (Iconarp International Journal of Architecture and Planning, 2020)
In today’s living conditions, the quality of life depends on well-managed energy. Therefore, countries produce different energy policies to manage their energy resources. Determining appropriate, feasible, and controllable energy policies becomes important especially for buildings, as being one of the most significant energy consumers. Green building certification systems (GBCSs) are one of the most common applications for energy efficiency in the building sector.